2016
DOI: 10.1080/13880209.2016.1211154
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil from fruit of Xylopia langsdorffiana: antitumour activity and toxicity

Abstract: EOX showed in vitro and in vivo antitumour activity and low toxicity, which warrants further pharmacological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…In addition, essential oils and their components, especially monoterpenes and phenylpropanoids, have shown antitumor activity [57, 39, 40]. Some of the constituents present in EOM are described in the literature as having significant antitumor activity, specifically limonene [41], β-caryophyllene [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, essential oils and their components, especially monoterpenes and phenylpropanoids, have shown antitumor activity [57, 39, 40]. Some of the constituents present in EOM are described in the literature as having significant antitumor activity, specifically limonene [41], β-caryophyllene [42].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, essential oils from plants have been useful in cancer prevention and treatment [57]. Its effects are associated with antioxidant, antimutagenic, antiproliferative, and immunostimulatory properties, besides modulating multidrug resistance [8].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of interesting pharmacological properties have been attributed to αpinene, including anti-inflammatory, bronchodilator, hypoglycemic, sedative, antioxidant, and broadspectrum antibiotic activities (Mercier et al, 2009;Violante et al, 2012;Da Silva et al, 2012). Previous studies have reported the presence of α-pinene in the essential oils obtained from Annonaceae family, such as Polyalthia korintii (leaf oil: 43.2%) (Sherin et al, 2018), Guatteria costaricensis (leaf oil: 36.3%) (Palazzo et al, 2009), and Xylopia langsdorffiana (fruit oil: 34.6%) (Moura et al, 2016). Meanwhile, germacrene D was also present as the predominant component in the oil.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the numerous studies that confirm the biological properties of essential oils and propose different applications for them, research into their toxicological and pharmacological characterization is necessary, in order to protect population health, in addition to the scientific proof of the therapeutic efficiency of these products …”
Section: Introductionmentioning
confidence: 99%